A taxonomic review of the dry-fruited species of Anemone (Ranunculaceae) in southern Africa - Manning, J.C.; Goldblatt , P. (African Biodiversity & Conservation, 2013)
The three dry-fruited species of Anemone sect. Pulsatilloides subsect. Alchemillifoliae (Ranunculaceae) from southern Africa are reviewed, with full descriptions and nomenclature, including complete synonomy, taxonomic history with nomenclatural corrections, ecological notes, and distribution. A. tenuifolia (L.f.) DC. from the Cape Floristic Region is segregated as ser. Pinnatifoliae from the two summer rainfall species, A. caffra (Eckl. & Zeyh.) Harv. and A. fanninnii Harv. ex Masters, which remain in ser. Alchemillifoliae, emphasising the strong vegetative differences between the two series.